Diagnostic Dilemma of Retroperitoneal Schwannomas Encountered in a Specialized Gynecology Hospital - Chunbo Li; Luopei Guo; Keqin Hua (Journal of Investigative Surgery, 2022)
Background: This study analyzed the potential diagnosis and therapeutic challenges of retroperitoneal schwannoma (RSs) in a specialized gynecology hospital. Methods and materials: A retrospective review was performed in our hospital from 2000 to 2018. A literature search of RSs was conducted using PubMed database. Results: 45 patients were identified (22 from our hospital and 23 from the literature review). The majority of patients presented asymptomatic (22/45). Among them, 25 cases were misdiagnosed as adnexal cysts, 13 uterine fibroids, 1 ovarian malignancy and 6 pelvic masses. Intraoperative exploration revealed that the masses were located in the retroperitoneal space. The median diameter was 6.2 cm (range 3.0–9.8 cm) in our hospital compared with 9.3 cm (6–15 cm) in literature review. Complete resection was performed in 37 patients and subtotal resection in 8 patients. The pathological results confirmed the diagnosis of benign schwannoma and no recurrence was found in the follow-up data. Conclusion: The preoperative diagnosis of RSs is difficult to make because of its nonspecific characteristics. In a specialized gynecology hospital, it is more important to differentiate the benign and malignant of mass before surgery. Surgical complete resection of tumor is recommended and recurrence is unusual after complete resection.